The Substantive Justice in Regional Elections: A Philosophical and Sociological Comparison of Asian, European, And African Countries - Nurlaily, Nurlaily; Minin, Agusta R.; Samararatne, Dinesha (Magister of Law, Faculty of Law, University of Mataram, 2025)
Substantive justice in regional elections, which focuses on election outcomes that reflect social justice, inclusiveness, and fair distribution of power, requires a contextual approach in Asia, Europe, and Africa to address the unique challenges of each region and create more inclusive and just political systems. This study aims to explore the philosophical and sociological understanding and application of the concept of substantive justice and its impact on political representation and inclusiveness in regional elections in Asian, European, and African countries. This study uses normative legal methods with legislative, conceptual, and comparative approaches to analyze the concept of substantive justice and its application in regional elections in Asia, Europe, and Africa, relying on qualitative analysis of primary, secondary, and tertiary legal materials. The results of the study show that substantive justice in regional elections focuses on outcomes that reflect social justice, equality, and inclusiveness, with highly contextual applications in Asia, Europe, and Africa. In Europe, this concept is influenced by John Rawls’ theory of justice as fairness, with a proportional electoral system that is effective in representing the diversity of society. In Asia, values ​​of social harmony and cultural plurality influence the implementation of substantive justice, although challenges such as money politics and social inequality remain significant. In Africa, the philosophy of Ubuntu encourages community solidarity, but obstacles such as corruption and ethnic conflict hinder its implementation. In general, affirmative action policies, ongoing reforms, and public education are needed to strengthen inclusiveness and political representation at the local level in various regions.